The importance of interdisciplinary approach to urban agriculture and transitions in food systems: Research on Lisbon Metropolitan Area - Ferreiro, M. F. (2019)
Metropolitan areas are strategic territories in the research on ‘urban agriculture, food and food systems’. Land use categories and farm related activities constitute major indicators in this research. One of the main characteristics of periurban areas is the complementary nature of the relations between urban and rural systems. The paper presents and discusses the main findings of two research projects conducted in Lisbon Metropolitan Area, in relation with urban agriculture and food and the transition of the food sociotechnical system. This presentation and further discussion highlights the adequacy of interdisciplinary approaches regarding ‘Connections and missing links within urban agriculture, food and food systems’.